EFESIENSI PELAYANAN PUBLIK BIDANG KESEHATAN PASCA PEMEKARAN WILAYAH DI PROVINSI KALIMANTAN BARAT - Putra, Windhu (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
This study aimed to see differences in the level of efficiency of health services between the district / city after the expansion area, which further meremuskan model of cooperation between regions in order to optimize efficiency. The study was conducted in 9 districts consisting of 4 district parent regions, namely; Pontianak district, Sambas district, Sanggau, Sintang. 5 autonomous regions and districts, namely; Singkawang City, Bengkayang District, Landak District, Sekadau District, Melawi District. By using analysis tools Data Envelopment Analysis (DEA) to compute efficiency at every hospital in the region and regional division, indicating differences in the level of efficiency of the hospital results in conditions before and after the expansion area, where levels of efficiency after the expansion is lower than that before the separation. Through the cluster model approach (Model Clusters) will improve the efficiency of hospital after separation, that is by revitalizing the efficiency based on the mobility of the Human Resources (HR) between regions.